POTENTIAL OF COW’S BLOOD AS A MOTORIZED VEHICLE EXHAUST EMISSION REDUCTION - Wulanawati, Armi; Sari, Silvia Mekar; Fachrurrazie, Fachrurrazie (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Motorized vehicle is a means of transportation needed to support various human activities. But on the other hand, this tool is the biggest contributor (85%) to the problem of air pollution that occurs in Indonesia. This is due to motorized vehicle exhaust emissions producing various kinds of pollutants, including hydrocarbon compounds (HC), carbon monoxide (CO), and nitrogen oxides (NOx) which are dangerous and toxic gases, and carbon dioxide (CO2) as a factor in global warming. Hazardous exhaust emissions are formed due to incomplete combustion in the working process of the motor due to a lack of oxygen gas supply. Therefore, it is necessary to find a way to overcome this impact, among others by adding additives that have a high oxygen content to the fuel. The oxygen source can be found abundantly in the blood because it contains hemoglobin, rich in oxygen. Be discovered, cow's blood from animal slaughter waste if it is directly disposed of without processing can also cause environmental pollution. Thus, this research was carried out by synthesizing additives from cow’s red blood cells mixed with methanol at a concentration of 0.1% (w/v) using a maceration time of 3 h. The use of these additives in motorized vehicle fuels resulted in reduced emissions of HC, CO, NOx, and CO2 respectively by 65.96%; 71.43%; 66.67%; and 36.15%. Keywords: cow's blood, exhaust emissions, motorized vehicles, air pollution